Economic and social upgrading in global value chains insights from Philippine manufacturing firms - Mendoza, Adrian R. (Philippine Journal of Public Policy: Interdisciplinary Development Perspective, 2018)
This study explores results of the 2012 Survey on Adjustments of Establishments to Globalization (SAEG) to analyze the economic and social upgrading experience of Philippine manufacturers within global value chains (GVCs). Three broad patterns emerge from the data. First, firms with stronger GVC linkages tend to have better labor indicators than purely domestic producers. Second, the majority of manufacturers either experienced or missed economic and social upgrading simultaneously. Lastly almost all social upgrading is accompanied by economic upgrading but economic upgrading may take place without a social component. Against this background, this study uses bivariate profit regression to model the joint determination of the two separate but interconnected upgrading outcomes. The results indicate that the covariates in the model can be categorized based on their statistical significance: purely economic (i.e., employment size, unit labor cost, high skill intensity, and the Kaitz dummy),purely social (i.e., training, female intensity, and foreign equity), and both (i.e. contractualization, and process and product innovations).